A Structural Model of Risk Governance and Maturity in Ultra Microfinance SOEs - Eko Susetyono; Dominicus Savio Priyarsono; Anggraini Sukmawati; Popong Nurhayati (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
The Indonesian government has set a target for State-Owned Enterprises (SOEs) to achieve a risk management maturity level of 4.2 out of 5 by 2024. This objective is especially crucial following the consolidation of BRI, Pegadaian, and PNM into the Ultra Micro SOEs Holding. The integration process introduces new risks that require robust governance and control mechanisms. This study investigates how key risk management components namely governance, frameworks, processes, and internal controls contribute to strengthening risk management maturity in the Ultra Micro holding structure. Using Structural Equation Modelling (SEM), the research explores complex interrelations among these elements based on survey data from 644 respondents across the three SOEs. The findings confirm that most variables significantly influence one another and collectively support a sound model for maturity enhancement. However, the study also uncovers two statistically insignificant relationships: between the framework and the process, and between the process and overall maturity. These anomalies indicate the potential presence of mediating variables or implementation gaps that reduce the practical effectiveness of formal structures. The study concludes that a strong foundation in governance and internal control can meaningfully support risk maturity, but effective process execution may require further contextual and operational alignment. These results offer strategic insights for improving risk practices in SOEs and emphasize the need for future research to investigate hidden dynamics that may affect risk maturity outcomes.